(3EOGQI GdHfhc (B((3c(B20) (3GdLRA GdKGfj (B/s - (3CHh RjO, MGeO GdOShbjs ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s, 1994)
(3HjFI GdYed GdOGNdjI ddHfc h JGKjQgG Ydi GdGOGA h GdJhRjY dNOeGJg, GdHjFI GdNGQLjI ddHfc h JGKjQgG Ydi GdGOGA h GdJhRjY ddNOeGJ GdebOeI ddYedGA, cjajI Gdhbha Ydi JGKjQ GdHjFI Ydi YedjGJ GdHfc, JNWjW CYeGd GdHfc, JfXje CYeGd GdHfc, JhLjg ebOej GdNOeGJ GdHfcjI, GdQbGHI Ydi GdGOGA GdYGe ddHfc, GdQbGHI Ydi GdNOeI GdHfcjI, GdJWHjb GdYedj ddQbGHI Ydi GdGOGA GdYGe ddHfc, bjGS hGSJNOGe JcdaI eUGOQ GdJehjd aj GdHfc, QHMjI GdHfc, SjhdI hCeGf YedjGJ GdHfc, eOi edGAeI QCS eGd GdHfhc, QjGVjGJ GdHfhc(B. s
(3eQGLY U(B.316s
Keywords: (3GdHfhcs; (3GdQbGHIs